Servant Leadership in Educational Enviroment toward Employee Performance: A Case of Universitas Katolik Indonesia Santu Paulus Ruteng, Indonesia - Hatam, Benedict Feliks; Dantes, Kadek Rihendra (FKIP Universitas Lampung, 2024)
Abstract: Servant Leadership in Educational Enviroment toward Employee Performance: A Case of Universitas Katolik Indonesia Santu Paulus Ruteng, Indonesia Kasus Universitas Katolik Indonesia Santu Paulus Ruteng, Indonesia. Contribution of Servant Leadership to Individual Performance in the Flores Islands, East Nusa Tenggara (NTT) , Indonesia. Objective : This research aims to determine the contribution of servant leadership to individual performance. This includes stating the most prominent indicators for each variable based on the research subject. Method : This research uses quantitative methods with an ex-post facto or non-experimental design. The population in this study was 66 educational staff at Unika Santu Paulus Ruteng, and sampling was carried out using saturated samples. Findings : Servant leadership contributes to employee performance. Apart from that, there are indicators of servant leadership and performance which are very influential in improving individual performance on the Flores Islands, NTT. Conclusion : Servant leadership contributes to individual performance in ex-post facto research using linear regression analysis methods. Keywords: servant leadership, employee performance.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202407